Bioética Clínica: Una capacitación indispensable para la práctica médica en el siglo XXI - Valle Mansilla, José Ignacio (2003)
The social changes that took place throughout western history, together with the technological sophistication that has characterized the medical work of the last three decades, had generated new and serious problems whose solution was not framed in the traditional knowledge of the medical education. Clinical Dioethics arose like a tool to the service of the professional excellence and today, a few inore than 30 yers of its origin, it has already a solid academic implantation.